Identification and characterization of human UDP‐glucuronosyltransferases responsible for the in vitro glucuronidation of bergenin. (2nd September 2013) - Song, Haojing; Wang, Jin; Zhang, Rui; Liu, Xiaoyan; Yuan, Guiyan; Wei, Chunmin; Wang, Benjie; Guo, Ruichen
ABSTRACT Glucuronidation plays critical role in the elimination of bergenin; however the metabolic mechanism of UDP‐glucuronosyltransferases (UGTs) in the process remains to be investigated. In this study, the kinetics of bergenin glucuronidation by pooled human liver microsomes (HLMs) and 12 recombinat UGT isozymes were investigated. The glucuronidation of bergenin can be shown in HLMs with a Km value of 231.62 ± 14.08 µm and a Vmax value of 2.17 ± 0.21 nmol/min/(mg protein). Among the 12 human UGTs investigated, UGT1A1 was identified as the major isoform catalyzing the glucuronidation of bergenin [Km value of 200.37 ± 26.73 µm and Vmax value of 1.88 ± 0.26 nmol/min/(mg protein)]. The bergenin glucuronosyltransferase activities in HLMs and UGT1A1 were inhibited by phenylbutazone, estradiol and bilirubin. The results demonstrate that bergenin glucuronidation in HLMs is specifically catalyzed by UGT1A1. Copyright © 2013 John Wiley & Sons, Ltd.